PERENCANAAN PEMBANGUNAN EKONOMI WILAYAH BERBASIS PERTANIAN DALAM RANGKA PENGURANGAN KEMISKINAN DI PROVINSI GORONTALO 2008-2019 - Wijaya, Narendra Maulana; Bintoro, Nugroho Suryo (Journal of Development Economic and Social Studies, 2024)
This research is motivated by the issue of high poverty rates in the Province of Gorontalo, as well as the low value added in the agricultural sector, reflected by the sluggish growth of the agricultural sector and the prevalence of poverty among the population employed in this sector. The aim of this study is to investigate how the growth of the agricultural sector and other control variables influence poverty reduction in the Province of Gorontalo. The research employs panel data analysis using data encompassing all districts/cities in the Province of Gorontalo over a span of 12 years. Poverty plays the role of the dependent variable, while the growth of the agricultural sector serves as the independent variable along with other control variables, namely agricultural basis/non-basis region dummies, Human Development Index, Economic Realization, and Open Unemployment Rate. The results indicate that the dummy variables for agricultural basis and non-basis regions, Human Development Index, and Economic Realization have a significant negative impact on poverty. However, the variable of agricultural sector growth has an insignificant effect, and the open unemployment rate also has an insignificant influence on poverty.